2009
DOI: 10.1139/t08-126
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale testing of draped nets for rock fall protection

Abstract: The installation of draped meshes, metallic nets installed in such a way as to lie against the rock slope surface, is one of the most common ways to protect roads and infrastructure against the detachment of small rock elements in areas prone to rock fall. Despite their frequent and worldwide application, there are no universally recognized guidelines or technical standards to help engineers in their correct design, and no full-scale test results are available where the whole system, composed of several intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 6 publications
1
45
0
Order By: Relevance
“…The critical energy for a flexible barrier is most reliably determined by physical tests (e.g., Smith and Duffy 1990;Hearn et al 1995;Peila et al 1998;Grassl et al 2002;Bertolo et al 2009;Arndt et al 2009;Hearn et al 1992;Buzzi et al 2012;Peila and Ronco 2009), however large costs and long set-up times have motivated a number studies in which block impact is simulated numerically (e.g., Anderheggen et al 2002;Cazzani et al 2002;Volkwein 2005;Cantarelli et al 2008;Buzzi et al 2011;Hearn et al 1995;Hearn et al 1992). In both tests and simulations, it has been observed that there is no single value of critical energy for a barrier but rather a range of critical energies corresponding to different block sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The critical energy for a flexible barrier is most reliably determined by physical tests (e.g., Smith and Duffy 1990;Hearn et al 1995;Peila et al 1998;Grassl et al 2002;Bertolo et al 2009;Arndt et al 2009;Hearn et al 1992;Buzzi et al 2012;Peila and Ronco 2009), however large costs and long set-up times have motivated a number studies in which block impact is simulated numerically (e.g., Anderheggen et al 2002;Cazzani et al 2002;Volkwein 2005;Cantarelli et al 2008;Buzzi et al 2011;Hearn et al 1995;Hearn et al 1992). In both tests and simulations, it has been observed that there is no single value of critical energy for a barrier but rather a range of critical energies corresponding to different block sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce rockfall risks in the upper quarry yards, and in particular on the access roads that lead to the mine shaft, the quarry manager has recently installed a number of safety measures, including drapery wire meshes, on the rock faces (Figure 7) (Bertolo et al, 2009). The QuaRRi method was applied to verify the specific local conditions of this portion of the quarry (Figure 8).…”
Section: Case Study Of a Limestone Quarrymentioning
confidence: 99%
“…This method, which can be considered a valuable tool, does not evaluate the falling block trajectory for each and every quarry geometry, and therefore does not directly compute the probability that a block will come into contact with a worker or machinery; furthermore, it does not take into due account the variability of rockfall phenomena, and particularly does not permit one to assess the positive effect of the installation of rockfall protection devices, such as drapery nets (Figure 2) or net fences (Figure 3), which, in the last few years, have been greatly improved for road and railway protection and are now starting to be widely used in mining activities (Peckover and Kerr, 1977;Peila and Oggeri, 2003;Peila et al, 2006;Ronco et al, 2009;and Bertolo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Common response types to rebound include bouncing, rolling, and sliding or a combination thereof [3]. To reduce rockfall disaster, various mitigation measures including wire anchors, rock bolts, intercepting ditches, SNS flexible nets, and attenuator systems have been extensively adopted [1,4,5]. e design of these rockfall mitigations is based on the trajectory of rockfall movement including bounce height, runout distance, kinetic energy, and lateral dispersion.…”
Section: Introductionmentioning
confidence: 99%